2019
DOI: 10.2147/ccide.s234335
|View full text |Cite
|
Sign up to set email alerts
|

<p>Self-Reported General and Oral Health in Adults in the United States: NHANES 1999-2014</p>

Abstract: Objective: To assess self-reported general health (SRGH) and self-reported oral health (SROH), and to identify factors associated with these self-health reports among adults in the United States. Methods: Data from the National Health and Nutrition Examination Survey (NHANES) for 1999 to 2014 were analyzed. Survey-weighted descriptive statistics were computed and Pearson correlations between the two self-reported health status measures were tested. Separate multivariable logistic regressions in SROH and SRGH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…There is much evidence that socioeconomic status is closely associated with oral health status, irrespective of the socioeconomic measure used [17,18]. A recent National Health and Nutrition Examination Survey study reported that age, race/ethnicity, education, and family income were significantly associated with the oral health status of Americans [18]. In this study, whites rated their oral health as poor more often compared to those from other racial groups.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…There is much evidence that socioeconomic status is closely associated with oral health status, irrespective of the socioeconomic measure used [17,18]. A recent National Health and Nutrition Examination Survey study reported that age, race/ethnicity, education, and family income were significantly associated with the oral health status of Americans [18]. In this study, whites rated their oral health as poor more often compared to those from other racial groups.…”
Section: Discussionmentioning
confidence: 61%
“…Poor oral health status among the respondents was associated with poor mental health, age, socioeconomic status, and not visiting the dentist at regular intervals. There is much evidence that socioeconomic status is closely associated with oral health status, irrespective of the socioeconomic measure used [17,18]. A recent National Health and Nutrition Examination Survey study reported that age, race/ethnicity, education, and family income were significantly associated with the oral health status of Americans [18].…”
Section: Discussionmentioning
confidence: 99%
“…4 Another large cross-sectional study from the same NHANES Survey (phases I-VIII, 1999-2014) also suggested that higher levels of education and income were associated with higher odds of reporting excellent or very good oral and general health. 3 Furthermore, Borrell and Baquero's study from the United States also reported higher levels of education and income to be positively associated with self-reported oral and general health. 23 The investigation led by Hakeberg and Boman 7 was conducted in a similar setting and reported similar ndings to our study, except for a steeper gradient in ORs for poor general health according to income level.…”
Section: Discussionmentioning
confidence: 94%
“…Oral health is an integral part of general health, 1,2 and a growing body of research has shown that both oral and general health vary with social determinants. [2][3][4][5][6] Good oral and general health are associated with higher socioeconomic status, and poor oral and general health with lower socioeconomic status. 4,7,8 These differences are often found to vary from top to bottom as gradients, with increasingly poor health with each lower category of the socioeconomic indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Such as the lack of diagnostic codes not been widely used and promoted in dentistry. Traditionally, dental Medicaid and commercial claims provide information on the financial expenditures associated with dental treatment (9)(10)(11) and self-reported measures documents individual's behavior, attitude, symptoms, and treatment received (12)(13). However, commercial and Medicaid claims data built on Current Dental Terminology (CDT) procedure codes could potentially be used to provide estimates on the prevalence for oral disease such as dental caries and periodontal disease in sub-populations who have dental coverage.…”
Section: Introductionmentioning
confidence: 99%